Paleo-ENSO influence on African environments and early modern humans - Kaboth-Bahr, Stefanie; Gosling, William D.; Vogelsang, Ralf; Bahr, André; Scerri, Eleanor M. L.; Asrat, Asfawossen; Cohen, Andrew S.; Düsing, Walter; Foerster, Verena; Lamb, Henry F.; Maslin, Mark A.; Roberts, Helen M.; et al. (Proceedings of the National Academy of Sciences of the United States of America, 2021)
In this study, we synthesize terrestrial and marine proxy records, spanning the past 620 ky, to decipher pan-African climate variability and its drivers and potential linkages to hominin evolution. We find a tight correlation between moisture availability across Africa to El Niño Southern Ocean oscillation (ENSO) variability, a manifestation of the Walker Circulation, that was most likely driven by changes in Earth’s eccentricity. Our results demonstrate that low-latitude insolation was a prominent driver of pan-African climate change during the Middle to Late Pleistocene. We argue that these low-latitude climate processes governed the dispersion and evolution of vegetation as well as mammals in eastern and western Africa by increasing resource-rich and stable ecotonal settings thought to have been important to early modern humans.
Gesehen am 25.10.2021